Reações adversas à poliquimioterapia em hanseníase - Franco, Lenise de Albuquerque (2014)
Leprosy is slowly progressive, chronic infectious disease, caused by the bacillus Mycobacterium leprae (M. leprae), with a potentially severe, mutilating and stigmatizing evolution. It represents a major public health problem in a lot of the countries around the world. Since 1982, the World Health Organization (WHO) recommended multidrug therapy (MDT) for the treatment of the disease with the combination of three drugs (rifampicin, clofazimine and dapsone) in multibacillary cases, and two, for the paucibacillary (rifampicin and dapsone). When more than one drug is used, the risks of adverse effects are increased. Retrospective papers reveal that adverse effects of drugs of MDT are one of the causes of irregularity or noncompliance with treatment, which make difficult the combat against the disease as a public heath problem. Furthermore, the occurrence of these events in an economically active age group may cause work absenteeism and be onerous. On other hand, spontaneous reports of adverse effects systems are at risk of subnotification, demanding the elaboration of specific forms of notification. Therefore, this paper aimed: 1) To verify the frequency and types of adverse effects to the drugs used on multidrug treatment (MDT) in two centers of reference in leprosy treatment, as well as the occurrence of serious adverse events leading to change in the treatment and its correlation with the presence of other diseases; 2) To identify clinical and epidemiological aspects of risk associated with the occurrence of adverse reactions and the instant of its appearance. 3) To analyze the risk of adverse effects interfere with treatment adherence, therapeutic response and the occurrence of leprosy reaction in patients followed in two referral centers treating leprosy. We designed a prospective study, after approval of the ethics committee, with monthly evaluation of the patients in two centers of leprosy treatment during the period of November 2011 and May 2014: in the ambulatory of (Des)Mancha-Sergipe Project, Universiy Hospital, Universidade Federal de Sergipe, and Reference Center of Leprosy, CEMAR (Centro de Especialidades Médicas de Aracaju). We applied a questionnaire to collect demographic, clinic, epidemiologic parameters such as sex, age, Body Mass Index (BMI), operational form of disease and adverse effects information in monthly evaluation, and analyzed their relationship to the therapeutic response, occurrence of leprosy reactions and treatment adherence. After the inclusion and exclusion criteria, we followed 119 of 245 patients that initiated the MDT between November 2011 and May 2013 in two centers. Adverse effects to MDT treatment were common, with a predominance of cutaneous related ones associated to clofazimina, such as ichthyosis/ xerosis (70.6%) and skin pigmentation (65.5%), followed by anemia related to dapsone (62.2 %). Although most adverse events to MDT were mild, severe adverse effects were detected, such as Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) in 3 patients, who required the suspension of MDT and replacement of dapsone for another drug, besides haemolytic anemia and drug hepatitis. Therapy was replaced in 13 patients, of whom 12 had at least 1 disease, which indicates probable use of other medications and suggests possible drug interaction as influence on adverse reactions, especially in the more severe. It was observed association of adverse effects to MDT with gender, age group, body mass index (BMI), operational classification and occurrence of leprosy reaction. The adverse effects did not impact on the adherence to treatment or therapeutic response. Thus, although retrospective papers show that adverse effects to drugs of MDT are important cause of irregularity or noncompliance with treatment, this present study was prospective, revealing that the active search for patients and specific adverse effect investigation forms can prevent leprosy treatment dropout.